Innovation Networks in the German Laser Industry Evolutionary Change, Strategic Positioning, and Firm Innovativeness - Kudic, Muhamed; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Technological innovation is fundamental to firm performance and economic prosperity. The aim of this book is to contribute to an in-depth understanding of collective innovation processes by analyzing publicly funded R&D cooperation and innovation networks in the German laser industry. Standing in a neo-Schumpeterian tradition, it employs interdisciplinary analytical concepts and draws upon a unique longitudinal dataset from the laser industry that covers more than two decades of observations. In brief, the book makes a valuable contribution by exploring how and why firm-specific R&D cooperation activities and network positions, large-scale network patterns, and evolutionary network change processes affect the innovative performance of laser source manufacturers in Germany.
Introduction and Theoretical Background: Introduction -- Theoretical Background -- Industry, Data and Methods: Laser Technology and the German Laser Industry -- Methodological Reflections and Data Sources -- Quantitative Concepts and Measures -- Dataset Design and Estimation Methods -- Descriptive Analysis: Industry Dynamics and Geographical Concentration -- Evolution of the Industry's Innovation Network -- Econometric Analysis: Causes and Consequences of Network Evolution -- Ego Networks and Firm Innovativeness -- Small World Patterns and Firm Innovativeness -- Network Positioning, Co-Location or Both? -- Summary, Conclusion and Outlook: Findings and Limitations -- Further Research and Conclusions.
Keywords: Management; Industrial management; Economic geography; Evolutionary economics; Industrial organization; Economic policy; Economic sociology; Economics; R & D/Technology Policy; Institutional/Evolutionary Economics; Innovation/Technology Management; Industrial Organization; Organizational Studies, Economic Sociology; Economic Geography; Electronic books